Snack bar berbahan pati sagu (Metroxylon sp.), tempe, dan beras hitam sebagai pangan fungsional berindeks glikemik rendah - Puspita, Winny; Sulaeman, Ahmad; Damayanthi, Evy (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Background: High calories intake from snacks with low nutritional value will contribute to increase the prevalence of obesity and diabetes. Nutritional strategies to prevent hyperglycemia are controlling blood glucose levels, restrict calories and carbohydrate intake. Sago starch (Metroxylon sp.), tempe and black rice contains ingredients such as dietary fiber, resistant starch, amylose and low glycemic index. Modified snack bar using these ingredients can produce attractive products and provide the beneficial nutrients.Objectives: To determine a snack bar formulation made from sago starch, tempe and black rice and analyze physicochemical characteristics and glycemic index value of the product.Methods: This study used a completely randomized design analyzing three different proportions of sago starch and tempe, namely F1 (2:1), F2 (1.5:1), and F3 (1:1) with two replications for each formula. The Selected formula was determined based on consumer acceptability by semi-trained panelists using 9-point hedonic scale, physicochemical properties, nutrient content, and glycemic index value. Results: The Selected formula (F3) was potentially used as functional food as indicated by high level of dietary fiber (11.05%), 8.8 % resistant starch, in vitro starch digestibility (14.02%), the highest amylose-amylopectin ratio (60.1% : 39.9%), low glycemic index (40) and low glycemic load (5.4). The F3 formula produced a slow increase and peak point of blood glucose response of 107.5 mg/dl at minute 30th lower than the administration of anhydrous glucose with peak point of blood glucose levels of 143.4 mg/dl.Conclusion: The F3 formula with the proportion of sago starch and tempe (1:1) had low glycemic index and was categorized as high-fiber food with high level of resistant starch. Therefore, this product has the potency as functional snack alternative for diabetes patients.